Health-related quality of life of Kuwaiti adults living with diabetes - Maryam S. Alowayesh; Syed Mohamed Aljunid; Syed Mohamed Aljunid; Afaf Aladsani; Thamer Alessa; Abdulnabi Alattar; Dherar Alroudhan (Frontiers Media S.A., 2023)
Diabetes is known to compromise patients' health-related quality of life (HRQoL). It is important to understand the HRQoL of Kuwaiti nationals living with diabetes and identify factors that negatively affect it. This study included 1,182 Kuwaiti nationals with diabetes, aged 18-80 years. Patients' demographic and HRQoL information was collected using the EuroQol EQ-5D-5L instrument. Mean values for each EQ-5D subscale were worst for mobility (1.9) and pain/discomfort (1.8). Most patients reported having no problems in self-care (84.4%). Older adults were most likely to report severe problems with mobility (p < 0.001). Females were more likely to report severe problems with anxiety and depression than males (p < 0.006). The EQ visual analog scale (EQ VAS), which reports perceived overall health on a 0-100 scale, showed a mean of 74.7 (±19.6). Patients with comorbidities and/or complications perceived their health to be worse, with VAS scores significantly lower (p < 0.001). Other factors that negatively affected VAS scores were being female, obesity, insulin usage, and lower levels of education. In conclusion, patients with diabetes who have comorbidities and/or complications perceived their health to be worse. Further research is required to evaluate if current diabetes management interventions help improve patients' HRQoL.